Intergroup time bias and racialized social relations - Vala, Jorge (2012)
Within the framework of intergroup relations, the authors analyzed the time people spent evaluating ingroup and outgroup members. They hypothesized that White participants take longer to evaluate White targets than Black targets. In four experiments, White participants were slower to form impressions of White than of Black people; that is, they showed an intergroup time bias (ITB). In Study 1 (N = 60), the ITB correlated with implicit prejudice and homogeneity. Study 2 (N = 60) showed that the ITB was independent of the type of trait in question (nonstereotypical vs. stereotypical). Study 3 (N = 100) demonstrated that ITB correlates with racism measured 3 months beforehand, is independent of motivation to control prejudice, and is not an epiphenomenon of homogeneity. In Study 4 (N = 40) participants not only showed the ITB in a racialized social context but also displayed it following a minimal group manipulation.